PEMIKIRAN TASAWUF HAMKA DAN RELEVANSINYA BAGI KEHIDUPAN MODERN - Salihin Salihin (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: One of the effects of modernization on religious life is a critical attitude toward religion. Religion, can only be accepted if; First, in accordance with the teachings sensible advancement of Science. Second, it could difunctional in answering the challenges of modernity. Hamka his popular book Modern Mysticism, which contains about how to build a happy life as desired by Islam. Thought Sufism Hamka not only meant the tarikat region alone but more than that, it is understood that Sufism in general can be interpreted according to its roots, which the teachings of Islam itself. The methodology used in this study were (1) the type of research; This type of research is the research library (Library Research) (2) of model approaches; Hermeneutic, use descriptive text or script interpretative against Sufism thought Hamka. While the main source is thought of Sufism Hamka as outlined in his books are: Modern Mysticism, Sufism development of Century Century and Mysticism development and purification. The thesis concludes that the essence of Sufism according to Hamka is aimed at improving the mind and cleanse the mind. Mysticism offered Hamka modern mysticism or Sufism is positive based on monotheism. Mystical path through the ascetic attitude carried on the official worship, ascetic attitude, which does not need to be away from normal life. So therefore, thought that dynamic Hamka Modern Mysticism extremely relevant to today’s modern life for a balance between worldly life and ukhrowi.